NABI MUHAMMAD SAW TOKOH PENDIDIKAN : Studi Analisis Makna Yang Tersirat Pada Surat al-Alaq Ayat 1-5 - romlah romlah; Sanuri Sanuri (Jurnal Pendidikan Educandum, 2021)
The Prophet Muhammad was able to build an advanced world civilization starting from the inspiration of khalwat in Hira Cave. The tangible result is that God commanded the prophet to build his ummah with education. Buya Syakur defines the word ummi as an indigenous person (native to Mecca). The word ummiy is illiterate, and it is the same as insulting the prophet as a messenger of God. Surah al-alaq verses 1-5 in it explain that the prophet Muhammad was an intellectual genius. This verse as information as well as evidence kalamullah that the prophet Muhammad has managed to change his ummah from a setback into a civilized nation advanced by studying various sciences